Serum Protein Profiling Reveals a Specific Upregulation of the Immunomodulatory Protein Progranulin in Coronavirus Disease 2019. (29th November 2020) - Rieder, Marina; Wirth, Luisa; Pollmeier, Luisa; Jeserich, Maren; Goller, Isabella; Baldus, Niklas; Schmid, Bonaventura; Busch, Hans-Joerg; Hofmann, Maike; Thimme, Robert; Rieg, Siegbert; Kern, Winfried; et al.
Abstract: Background: Severe courses of coronavirus disease 2019 (COVID-19) are associated with elevated levels of interleukin 6 (IL-6). However, there is a growing body of evidence pointing to a broad and more complex disorder of proinflammatory and antiviral responses with disturbed interferon signaling in COVID-19. Methods: In this prospective, single-center registry, we included severe acute respiratory syndrome coronavirus 2 (SARS-CoV-2)–positive patients and patients with similar symptoms and severity of disease but negative for SARS-CoV-2 admitted to the emergency department and compared their serum protein expression profiles. Results: IL-6 abundance was similar in SARS-CoV-2–positive patients (n = 24) compared with SARS-CoV-2–negative controls (n = 61). In contrast, we observed a specific upregulation of the immunomodulatory protein progranulin (GRN). High GRN abundance was associated with adverse outcomes and increased expression of IL-6 in COVID-19. Conclusions: The data from this registry reveal that GRN is specifically upregulated in SARS-CoV-2–positive patients while IL-6 may serve as marker for disease severity. The potential of GRN as a biomarker and a possible impact of increased GRN expression on interferon signaling, virus elimination, and virus-induced lung tissue damage in COVID-19 should be further explored. Abstract : Specific upregulation in coronavirus disease 2019 warrants further evaluation of progranulin as a potential biomarker and its impact on interferon signaling, virus elimination, and virus-induced lung tissue damage.